2011
DOI: 10.1007/s00508-011-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Konsensus Diagnose und Therapie von Weichteilsarkomen

Abstract: Soft tissue sarcomas are heterogeneous tumours and relatively uncommon. There have been advances over the past years concerning pathology, clinical behaviour, diagnosis strategies and the treatment. To summarize these advances as well as making it public is one of the goals of the following consensus guidelines. But why do we need special guidelines for Austria? There are international guidelines published by the European Society of Medical Oncology (ESMO) and the National Comprehensive Cancer Network (NCCN). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Adjuvant radiotherapy is recommended in borderline and malignant PTs with tumor-free margin < 1 cm [ 23 ]. For high-risk malignant tumors (higher grade, size > 5 cm), adjuvant radiotherapy is considered after R0 resection and recommended after R1 resection [ 24 ]. According to Chao et al, a meta-analysis with 696 patients enrolled in 17 studies, they found radiotherapy is effective in achieving local disease control and preventing metastasis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy is recommended in borderline and malignant PTs with tumor-free margin < 1 cm [ 23 ]. For high-risk malignant tumors (higher grade, size > 5 cm), adjuvant radiotherapy is considered after R0 resection and recommended after R1 resection [ 24 ]. According to Chao et al, a meta-analysis with 696 patients enrolled in 17 studies, they found radiotherapy is effective in achieving local disease control and preventing metastasis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiation therapy is recommended for borderline and malignant PTs with a tumor-free margin of 1 cm or greater [ 57 ]. Adjuvant radiation is recommended after R1 resection and indicated after R0 resection for high-risk malignant tumors (higher grade, size > 5 cm) [ 58 ]. Radiation-induced secondary sarcoma limits the clinical application of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Standard gross description parameters include the following: (1) measuring the specimen in three dimensions, (2) giving the closest distance of each margin from the edge of the tumour in millimeter (mm) or centimeter (cm), (3) the tumour relationship with anatomical structures, (4) the depth (subcutis, fascial, intramuscular) of the tumour, (5) the size of the tumour, and (6) presence of necrosis, as percentage of the total tumour. Individual blocks need to be taken from the margins and generally one block per cm of the maximum diameter of the neoplasm needs to be taken for histologic evaluation [5][6][7]. A photo documentation of a representative cross section is always helpful (Figs.…”
Section: Gross Descriptionmentioning
confidence: 99%
“…For other STT the line of differentiation, despite extensive IHC (immunohistochemistry), cannot be assessed leaving these tumours in the "undifferentiated" sarcoma cat-egory. Finally one must be aware that another subset of sarcomas can be classified based on their genetic fingerprint in combination with H&E morphology and IHC ( [7]; Fig. 1).…”
Section: Tumour Classificationmentioning
confidence: 99%